The effect of transformational leadership style in crisis management: does gender matter? - Mohd@Ariffin, Juliza Adira; Md Rami, Ahmad Aizuddin; Abd Wahat, Nor Wahiza; Muhamad Nasharudin, Nurfazreen Aina (Macrothink Institute, 2022)
Leadership qualities in crisis management have become an important aspect to ensure the effectiveness of organizations in dealing with crises. According to Shift 8 for education at the primary to secondary school level and Shift 6 for higher education, the government emphasizes the need to transform the capabilities and capacity of leaders in an educational organization in Malaysia. One of the capabilities needed by the leaders in educational organizations to perform their job nowadays is crisis management competencies. Despite the importance of leadership skills in crisis management, there has been few research focused on this topic, particularly in educational institutions. Because of that, this research has been conducted to bridge this gap. The primary goal of this study is to investigate the implementation of a transformational leadership style by leaders during crisis management in their organisation as well as the impact of the implementation on subordinates and the influence of gender on the implementation of that style. Qualitative methods which are interviews through Focus Group Discussion (FGD) were conducted involving six (6) informants from different educational institutions to identify themes. Studies have shown that, among the four characteristics of transformational leadership, only three of them, which are idealized influence, inspirational motivation, and intellectual stimulation, were regularly practised by the leaders, with less implementation of the characteristics of individualized consideration during crisis management. The findings also show that transformational leadership positively impacts subordinates during times of crisis. In addition, the gender of the leader had a significant impact on the findings, with male leaders demonstrating more transformative leadership styles during crisis management than female leaders. Finally, this study's findings will contribute to a field of study in which many educational institutions can use them as a guide to evaluate and improve the quality of their future leaders.